The Effect Of Multiple Role Conflicts, Work Stress And Motivation On The Performance Of Female Employees Of PT. Starlight Garment Semarang - Nurmiyati Nurmiyati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
One of the most crucial components of any business or organization is its human resources; these people are what set the company on its path to success. Employees must be able to provide their best work for the organization. Since employee performance, whether good or bad, affects a company's objectives and level of success. This study sought to ascertain the impact of numerous role conflicts, work-related stress, and motivation on female employees' performance at PT. Starlight Garment Semarang. The approach of quantitative research is implemented through the use of surveys, or data collection methods. Purposive sampling, or sampling with specific concerns, is a technique used in data collection methods. Non-probability sampling is the method utilized, and a sample of 75 responders is the result. The findings demonstrated a substantial relationship between job stress, motivation, and multiple role conflict and employee performance indicators. Employee performance is impacted by a number of role conflict variables, work stress, and motivation all at once. Based on the study's findings, it can be said that female employees' performance is partially and simultaneously impacted by the variables of numerous role conflicts, job stress, and motivation.